Pengaruh Keaktifan Masyarakat Dalam program Bank sampah Terhadap tingkat kesejahteraan - Sunendra Sunendra; Risma Listiani; Dzuliani Faseha; Bayu Adi Laksono (Program Studi Pengembangan Masyarakat Islam, 2022)
Community activity in the waste bank program is very important in addition to increasing public awareness in protecting the environment but also influencing the level of community welfare. If the community does not actively participate in the Waste Bank program, waste processing will experience obstacles, and can cause environmental problems caused by waste such as floods that can interfere with daily activities. These obstacles can affect the level of community welfare. The purpose of this study is to determine the effect of community activity in the Waste Bank program on the level of welfare. The research was carried out in Mulyasari Village, Tawang District, Tasikmalaya City. This study uses a quantitative approach with a sample size of 14 respondents. The results of the descriptive research show that there is a significant effect between the dependent variable on the independent variable. The conclusion generated is based on the results of the study that there is a positive and significant influence between community activities in the Waste Bank program on the level of community welfare. This is indicated by the value in the result of the sig value. ,000 < 0.05. This means that the higher community activity in the Waste Bank program, the level of community welfare will increase.